Interest Rates, Leverage, and Investor Rationality - Krainer, Robert E. (Journal of Financial and Quantitative Analysis, 1977)
An important maintained hypothesis in financial economics states that the average interest rate on a firm's debt is positively related to its leverage. This hypothesis has a long history going back at least to the work of Kalecki [4] where it was used to derive a determinate size for the competitive firm when the production function is homogeneous of degree one. The upward sloping interest rate-leverage relationship has also played an important role in the theory of finance. In this connection, it is somewhat interesting to find both Modigliani-Miller [5] and their many critics in complete agreement on the nature of this relationship. In particular, their statement on this subject conveys the impression that this relationship is governed by an unalterable law when they write: “Economic theory and market experience both suggest that the yields demanded by lenders tend to increase with the debt-equity ratio of the borrowing firm” [5, p. 273].